Analysis of Internet Traffic Using Average Daily Peak Hour (ADPH) - Hutomo, Fajar; Astuti, Yenni (SENATIK STT Adisutjipto, 2018)
In this era, Internet for education is one of the basic need; for students, teachers, lecturers, and staff. The increasing of internet needs cause the increasing of data traffic than before. In this research, traffic volumes of the Internet is analyzed using the ADPH (Average Daily Peak Hour) technique. ADPH is one of teletraffic techniques to calculate traffic volumes based on its busy hours. Previously, this technique is used in telephony systems. In this research, ADPH is tried to be used for calculating data traffic volumes.